Conditions for Innovation of Public Sector Organisations Based on Selected Primary Schools - Wodecka-Hyjek, Angelika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The aim of this article is to present and analyse the results of pilot studies relating to the diagnosis and evaluation of conditions for innovation of public sector organisations based on selected primary schools operating in a large city in Małopolskie Voivodeship, Poland. Research Design & Methods: The theoretical part of the article was based on the literature on the subject, both Polish and foreign. The pilot study was carried out by means of a guided, semi-structured interview with 17 teachers from four primary schools in Małopolskie Voivodeship, Poland. Undoubtedly, the results of the study have numerous limitations, which result mainly from the pilot nature of the survey and its limited scope (only selected teachers from four primary schools in a large city were willing to participate in the survey and were interviewed). Therefore, the results cannot be generalised and their analysis should be approached from a critical perspective. Findings: In the schools analysed, both the teachers and the management are aware of the importance of innovations in building the position of the school on the market of educational services, as well as of the fact that they are a key factor in teachers’ personal development. The innovation policy in the schools was generally known, while teachers are inspired to seek and implement innovations, and the attitude of the management in the majority of cases stimulates the creativity of the teachers, which is additionally supported by tangible or intangible incentives, e.g. commendations or awards. Implications / Recommendations: New ideas and solutions undoubtedly improve the teaching process, which is appreciated both by students and by their parents. In the primary schools participating in the study, the most important sources of innovation were the teachers, their level of knowledge, competence, creativity, commitment and personality. Contribution: Given the clear need for changes in the education sector, the study of innovation in primary schools is important and insufficiently recognised in Poland.